KONTRIBUSI DI TENGAH ARUS KONTROVERSI: Pesantren LDII Millenium Alfiena Nganjuk - Moh. Ashif Fuadi (Jurnal Al-Hikmah: Jurnal Dakwah, 2022)
This research discusses the history of the Alfiena Millennium LDII Islamic Boarding School. The problems that the author discusses are about the beginning of the establishment of pesantren, the existence and controversy of pesantren and the Indonesian Islamic Da'wah Institute (LDII), and the contribution of pesantren to the development of society and the government. The author uses a historical research method that starts from the selection of topics, the collection of historical sources, verifying sources, interpretation, and writing of history.  This research resulted in the conclusion that the LDII Millennium Alfiena Islamic Boarding School is an Islamic educational institution that was initiated in 1996 by K.H. Seger Afandi Al-Choir. The condition of the Pesantren in 1998 has given rise to the trust of the community and the government to grant permission for establishment. Despite experiencing many obstacles and obstacles, the Alfiena Millennium Islamic Boarding School can develop well and can carry out communication, work, and contributions. It is proven by the contribution of the Alfiena Millennium Islamic Boarding School to LDII residents and the general public.